2014
DOI: 10.1002/bab.1144
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterioplankton community and its antibiotic resistance genes in the Baltic Sea

Abstract: The residues from human environments often contain antibiotics and antibiotic resistance genes (ARGs) that can contaminate natural environments; the clearest consequence of that is the selection of antibiotic-resistant bacteria. The Baltic Sea is the second largest isolated brackish water reservoir on Earth, serving as a drainage area for people in 14 countries, which differ from one another in antibiotic use and sewage treatment policies. The aim of this study was to characterize the bacterioplankton structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The group has characterized the bacterioplankton structure and quantified antibiotic resistance genes within the bacterioplankton community of the Baltic Sea. The results of this study are described in the paper by Tiirik et al and revealed that all resistance genes targeted in the study were detectable from the Baltic Sea bacterioplankton. We suppose that this paper will be interesting not only to the specialists in microbial ecology and those who are working at wastewater treatment plants but also for each of us because, as mentioned by the authors of this research, antibiotics and antibiotic resistance genes are contained in the residues from human environments and can contaminate our main water reservoirs.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The group has characterized the bacterioplankton structure and quantified antibiotic resistance genes within the bacterioplankton community of the Baltic Sea. The results of this study are described in the paper by Tiirik et al and revealed that all resistance genes targeted in the study were detectable from the Baltic Sea bacterioplankton. We suppose that this paper will be interesting not only to the specialists in microbial ecology and those who are working at wastewater treatment plants but also for each of us because, as mentioned by the authors of this research, antibiotics and antibiotic resistance genes are contained in the residues from human environments and can contaminate our main water reservoirs.…”
supporting
confidence: 65%
“…One important study was performed by a research group of Jaak Truu from the University of Tartu, Estonia . The group has characterized the bacterioplankton structure and quantified antibiotic resistance genes within the bacterioplankton community of the Baltic Sea.…”
mentioning
confidence: 99%
“…Placed within the context of these studies, it can be determined that drinking water ARG gene copy numbers observed in the California cities studied are generally higher than those recorded in lakes, rivers, and bays in locations ranging from Manila 49 to China 33 and Colorado 31 among others. Water bodies similar in order of magnitude to cities in California have been recorded in an urban and industrial river, 50 sites along the Baltic Sea, 51 Swiss lakes, 52 and in drinking water treated from Lake Taihu, China. 53 However, nearly all drinking water samples obtained from Los Angeles, CA, exceed these reported values by nearly an order of magnitude.…”
Section: Resultsmentioning
confidence: 97%
“…They have been used for a wide range of studies, including to investigate the ability of DNA metabarcoding to indicate the fish species present in water and to analyse the structure of bacterioplankton communities (Tiirik et al 2014); it is the sequencing platform of choice for the EMP .…”
Section: Illuminamentioning
confidence: 99%